2008
DOI: 10.1111/j.1469-8137.2008.02586.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the transcriptomes of Populus trichocarpa and Arabidopsis thaliana suggests extensive evolution of gene expression regulation in angiosperms

Abstract: Summary• Sequencing of the Populus trichocarpa genome creates an opportunity to describe the transcriptome of a woody perennial species and establish an atlas of gene expression. A comparison with the transcriptomes of other species can also define genes that are conserved or diverging in plant species.• Here, the transcriptome in vegetative organs of the P. trichocarpa reference genotype Nisqually-1 was characterized. A comparison with Arabidopsis thaliana orthologs was used to distinguish gene functional cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 46 publications
5
35
0
Order By: Relevance
“…However, broadly expressed (i.e., combined breadth above 80%) gene pairs did have a significant nonlinear relationship between expression distance and d N /d S . Previous studies in Populus revealed that more broadly expressed genes tend to be predominantly cis regulated, while trans regulation drives more tissue-specific expression (Quesada et al 2008;Drost et al 2010), a finding that is broadly consistent with our results. Our data further suggest that expression divergence in broadly expressed genes may be reflected in coding sequence polymorphisms as well as variation in cis regulatory domains in noncoding regions.…”
Section: Expression and Sequence Divergence Correlated For Broadly Exsupporting
confidence: 82%
“…However, broadly expressed (i.e., combined breadth above 80%) gene pairs did have a significant nonlinear relationship between expression distance and d N /d S . Previous studies in Populus revealed that more broadly expressed genes tend to be predominantly cis regulated, while trans regulation drives more tissue-specific expression (Quesada et al 2008;Drost et al 2010), a finding that is broadly consistent with our results. Our data further suggest that expression divergence in broadly expressed genes may be reflected in coding sequence polymorphisms as well as variation in cis regulatory domains in noncoding regions.…”
Section: Expression and Sequence Divergence Correlated For Broadly Exsupporting
confidence: 82%
“…RNA extracted from these samples was used for microarray analyses with a custom-designed NimbleGen array containing features representing 55,793 annotated gene models from the sequenced genome of Populus trichocarpa, including 45,555 predicted gene models reported previously (Tuskan et al, 2006) plus an additional 10,238 gene models showing evidence of transcription (Quesada et al, 2008). Transcripts showing significant differences in abundance at a false discovery rate (FDR; Storey and Tibshirani, 2003) of 5% between adjacent time points (0-6 h, 6-24 h, and 24-48 h) were identified.…”
Section: The Poplar Transcriptome Is Remodeled In the Base Of Excisedmentioning
confidence: 99%
“…In primates, mutations that diversify the transcriptional regulation of genes expressed in multiple organs are more likely to be eliminated by negative selection (21). Similarly, orthologs expressed in multiple compartments in Arabidopsis and Populus are more likely to be expressed at similar levels, compared with genes that are specific to a single tissue or organ in both species (22). An extension of these observations would suggest that for genes in which eQTL are detected in multiple organs, the genetic regulation may be more conserved compared with those that are organ specific, which could evolve more rapidly by establishing alternative, trans-acting genetic mechanisms of regulation.…”
mentioning
confidence: 99%